Pemeriksaan Operasional Untuk Menilai Efisiensi Biaya Pemeliharaan Kendaraan Pada Pdam Tirta Pakuan Kota Bogor - Triandi, Triandi; Sembiring, Nahur Pakam (Jurnal Ilmiah Ranggagading (JIR), 2008)
Operational inspection is inspection directed to operation or management performance. One of its objectives is to evaluate efficiency, effectiveness, and economical aspect of operation, specifically to evaluate cost efficiency of vehicle maintenance at PDAM Tirta Pakuan Kota Bogor. The researchers uses descriptive method pointing to case study at PDAM Tirta Pakuan Kota Bogor. This descriptive method is intended to analyze available data. In operational inspection on vehicle maintenance at PDAM Tirta Pakuan Kota Bogor, there are seven phases of inspection, namely planning, introductional survey, preceding inspecting draft, provisional inspecting finding, detailed inspecting procedure, inspecting outcome, and inspecting outcome reporting. Based on the seven phases mentioned above, it can be concluded that sub-division of vehicle affairs has had reliable procedure and stipulation. The carrying out of operational inspection was done using inspection phases. The cost realization of vehicle maintenance could be said as proper. Keywords: Operational inspection; Cost efficiency of vehicle maintenance.